NILAI-NILAI SUFISTIK DALAM SURAT LUQMAN AYAT 12-19 (KAJIAN TAFSIR AL-JAILANI) - Muhammad Tarmidi (Pascasarjana IAIN Syekh Nurjati Cirebon, 2022)
The development of Qur’an interpretation started from the time of the Prophet, his companions, tabi'in, and tabial-tabi'in, The dominant interpretation of the Qur'an were the tafsir of bi al-ma'tsur, and tafsir bial-ra'yi,. However, according to some scholars of the Qur'an, the interpretation of Al-Qur’an is mapped into three, namely the interpretation that refers to the history (bi al-ma'sur), based on the reasoning (bi al-ra'yi), and using an intuition (bi al-isyari). Furthermore, among the three sources of interpretation above, the interpretation of intuition (bi al-isyari) is called Sufi interpretation. Tafsir Al-Jailani is one of Sufi interpretation. This paper aims to study the Sufi values in surah of Luqman. In this research, the author uses the method of literature study with a philosophical approach. The source of data in this study comes from tafsir with a Sufi pattern. The conclusion can be drawn is that in surah of Luqman 12-19 there are sufistic values namely: 1) The Meaning of Wisdom, 2) The Meaning of Gratitude, 3) The Meaning of Shirk, 4) Gratitude to Parents, 5) Following the Path of the Repentant, 6) Amar Ma'ruf Nahyi Munkar, 7) The Meaning of Patience, 8) Arrogant Deeds, and 9) The Meaning of Lowering Voice.Keywords: Sufism, Tafsir Al-Jailani, Surah Luqman